Biomechanical comparison of microvascular anastomoses prepared by various suturing techniques. Issue 12 (December 2020) - Szabo, Balazs; Fazekas, Laszlo; Ghanem, Souleiman; Godo, Zoltan A.; Madar, Jozsef; Apro, Aniko; Nemeth, Norbert
Highlights: Biomechanical parameters of anastomoses are not well studied. But, these parameters can show previously unknown properties of anastomoses. We found that the pressure drop is not correlated with the stitch count. One incorrectly placed stitch can dramatically increase the leakage. We showed that the tensile-strength of the vessel is decreased by the anastomoses. For the given vessel diameter more than 8-stitch should be used. Abstract: Introduction: The biomechanical properties of small vessels and microvascular anastomoses have not been studied completely yet. However, in case of vascular injury and various microsurgical reconstructive procedures a safe anastomosis is essential. Quick and reliable tests are needed to test various anastomoses in research and in teaching courses as well for quality control and proper feedback. We aimed to compare selected biomechanical properties of the simple interrupted, the continuous suture and the modified Lauritzen's sleeve-technique. Materials and methods: Sixty femoral arteries from chicken thigh biopreparates and 12 abdominal aortas from rats were used in this study. In case of the pressure resistance test the groups were: the simple interrupted, the continuous suture and the modified Lauritzen's sleeve-technique. The tensile-strength, elongation and elasticity measurement groups were the simple interrupted and continuous sutures with 8 and 12 stitches. Furthermore the suture materials in various conditions (simple thread, knotted threads, stitch with intact and damaged threads) were also compared. The tensile-strength and the pressure probe devices were custom made in cooperation with the Faculty of Informatics. Results: The average diameter of the chicken femoral arteries was 3.25±0.38 mm. The sleeve-technique showed the biggest pressure drop (56±16.41 mmHg), however, it was the fastest method. The tensile-strength of simple interrupted suture was 4.55±0.7 Newton (N), being lower than of the intact vessel (6.8 ± 1.4 N). The tensile-strength did not differ significantly between the 12-stitch simple interrupted and continuous sutures, however, the latter was stronger. The anastomoses made on thread model were significantly stronger than the ones on vessels. Conclusion: The main variables were the number of stitches and the strength of the vessel. The pressure drop was not correlated with the stitch number. One incorrect stitch can dramatically increase the leakage. Although the sleeve-technique is quick to be performed, it cannot withstand high pressure. The suture material itself is far stronger then the vessel. The vessel tensile strength was decreased in the anastomoses. For the given vessel diameter more than 8 stitches should be used.